Private equity challenge - acquiring Vetropack - Mendes, Carolina Clemente Rosa (2022)
This Work Project, in the form of an Investment Committee Paper was prepared by 4 students and consists of a proposal for a leveraged buy out of Vetropack Holding AG, a food and beverage glass pack aging manufacturer based in Switzerland with top european performance in particular in Central Europe. Following a deep analysis of the market and the company it was possible to identify growth opportunities vertical and horizontally to develop a strong value creation strategy backed by an optimal capital structure to realize an IRR of 25.9% and a Money Multiple of 4.9 x over the 7- year holding period.